2017
DOI: 10.1016/j.bbadis.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of aberrant PI3K/Akt signaling by Salubrinal in a GalT-deficient mouse model

Abstract: Classic Galactosemia is an autosomal recessive disorder caused by deleterious mutations in the GALT gene, which encodes galactose-1 phosphate uridylyltransferase enzyme (GALT: EC 2.7.7.12). Recent studies of primary skin fibroblasts isolated from the GalT-deficient mice demonstrated a slower growth rate, a higher level of endoplasmic reticulum (ER) stress, and down-regulation of the Phosphoinositide 3 kinase/Protein kinase B (PI3K/Akt) signaling pathway. In this study, we compared the expression levels of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…Kim et al, has confirmed the pivotal role of PTEN–PI3K signalling in the activation of primordial follicles [60]. We propose that dysregulation of the PTEN–PI3K signalling pathway in galactosaemia patients was identified in our studies and in the Gal deficient mouse model may be implicated in the primordial follicular dysgenesis observed in galactosaemia (Figure 1b) [17,18].…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Kim et al, has confirmed the pivotal role of PTEN–PI3K signalling in the activation of primordial follicles [60]. We propose that dysregulation of the PTEN–PI3K signalling pathway in galactosaemia patients was identified in our studies and in the Gal deficient mouse model may be implicated in the primordial follicular dysgenesis observed in galactosaemia (Figure 1b) [17,18].…”
Section: Introductionsupporting
confidence: 76%
“…The up-regulation of PTEN was also demonstrated in the human GC study of Coss et al (2014), as described earlier [17]. Salubrinal, a chemical compound that alleviates ER stress when administered to mutant mouse fibroblast cell lines normalised the down regulated PI3/Akt signalling pathway and the premature loss of primordial follicles seen in young mutant mice [18].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Previously, FSH treatment was found to activate the mTOR pathway and inhibit autophagy, but this effect was abolished in the presence of an AKT phosphorylation inhibitor [ 54 ]. In a previous report, there was an association between aberrant mTOR/Akt signaling and galactosemia [ 55 ]. According to the results reported here, we suggest that galactose stress induced miR-223, which targeted β1 integrin expression and resulted in impairing AKT phosphorylation and the downstream mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%